2020
DOI: 10.1152/ajpregu.00044.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cx30.2 deletion causes imbalances in testicular Cx43, Cx46, and Cx50 and insulin receptors. Reciprocally, diabetes/obesity alters Cx30.2 in mouse testis

Abstract: Cx30.2 protein content and localization were assessed during development. An account of Cx30.2, Cx43, Cx46, and Cx50, and insulin receptor (IR) responses to Cx30.2, Cx46, or Cx50 deficiency in mouse interstitial tissue (ITf)- and seminiferous tubule-enriched fractions (STf) is given. The impact of high glucose/insulin on Cx30.2 was investigated in spontaneously diabetic and obese db/db and ob/ob mouse testis and anterior pituitary (AP). Cx30.2 labeled contacts in vascular endothelial and Leydig cells and Serto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The mouse interstitial tissue contains both insulinT and insulin2 whereas tubules contain chiefly insulin 2 ( Pelletier et al, 2020a ). The drop in glucose in presence of elevated insulin2 concentrations evidences a normal response to insulin in tubules in contrast to the interstitial tissue-fractions in which the elevated insulin2 levels were not accompanied by a decrease in glucose in Pcsk9 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mouse interstitial tissue contains both insulinT and insulin2 whereas tubules contain chiefly insulin 2 ( Pelletier et al, 2020a ). The drop in glucose in presence of elevated insulin2 concentrations evidences a normal response to insulin in tubules in contrast to the interstitial tissue-fractions in which the elevated insulin2 levels were not accompanied by a decrease in glucose in Pcsk9 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on postnatal development were carried out on the same 7- to >60-day-old male mice or >60 days adult of BALB/cJ background that we used and described earlier ( Pelletier et al, 2015 ; Pelletier et al, 2018 ; Pelletier et al, 2020a ; Pelletier et al, 2020b ). Three animals were used per age group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both TEM and permeability assay showed that BTB integrity was compromised in this model ( Fan et al, 2015 ). In the mouse testis, IF localization of Cx43, Cx46 and Cx50 was analyzed using models of diabetes and obesity ( Pelletier et al, 2018 ; Pelletier et al, 2020 ). 10.…”
Section: Background: Mammalian Spermatogenesis and Btbmentioning
confidence: 99%